Sedentary Behavior During The COVID-19 Pandemic: An Electronic Survey Study In A Brazilian Small Urban Center - Teixeira , Gabriella Jenniffer Oliveira de Freitas (2025)
Introduction: It is unclear how public health restrictions due to the COVID-19 pandemic have influenced the sedentary behavior (SB) of adults in small urban centers. Aim: This study analyzed the SB of adults before and during the COVID-19 pandemic in a small urban center located in Brazil’s Northeast region. Methods: An electronic survey was carried out using the non-probability sampling method, in which 76 respondents (76.7% women, 18-57 years) met the eligibility criteria. SB was evaluated as the time spent (h/day) in a sitting or reclining posture activities (domains: Work/study; Leisure; TV; and Commuting). Results: The prevalence of SB was high both before (60.5%) and during the pandemic (59.2%), with no significant difference, regardless of the domain (P>0.05). Total time in SB before (9.4 h/day) and during (10.6 h/day) the pandemic was statistically similar (∆= +12.3%, P= 0.465). Conclusion: Despite the high prevalence of SB, public health restrictions imposed during the pandemic of COVID-19 did not appear to significantly alter SB patterns among the population under analysis.